Penggunaan Kahoot sebagai media evaluasi untuk meningkatkan minat belajar - Ar Ramadhan, Dzakwan Haidar; Milla, Sri Nurul; Hakim, Nurman (Program Studi Magister Pendidikan Agama Islam, 2025)
The low level of students' learning interest in Al-Qur’an Hadith subjects has become one of the challenges that must be addressed, particularly in grade XI at MAN 1 Kota Bogor. This study aims to determine the effect of using the Kahoot application as an interactive evaluation medium on increasing students' learning interest. The research employed a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The sample consisted of two classes: the experimental class used Kahoot, while the control class used conventional evaluation methods. The data collection instrument was a learning interest questionnaire that had been tested for validity and reliability. The results showed a significant difference between the two classes, where students using Kahoot experienced a greater increase in learning interest compared to those evaluated using conventional methods. The use of Kahoot proved to be effective in creating a more enjoyable, interactive learning atmosphere and in motivating students to participate more actively in the learning process. Abstrak Rendahnya minat belajar siswa dalam pembelajaran Al-Qur’an Hadis menjadi salah satu tantangan yang perlu segera diatasi, khususnya di kelas XI MAN 1 Kota Bogor. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan aplikasi Kahoot sebagai media evaluasi interaktif terhadap peningkatan minat belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen Nonequivalent Control Group Design. Sampel terdiri dari dua kelas, yaitu kelas eksperimen yang menggunakan Kahoot dan kelas kontrol yang menggunakan metode evaluasi konvensional. Instrumen pengumpulan data berupa angket minat belajar yang telah diuji validitas dan reliabilitasnya. Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan antara kedua kelas, di mana siswa yang menggunakan Kahoot mengalami peningkatan minat belajar lebih tinggi dibandingkan siswa dengan evaluasi konvensional. Penggunaan Kahoot terbukti efektif dalam menciptakan suasana pembelajaran yang lebih menyenangkan, interaktif, dan memotivasi siswa untuk lebih aktif terlibat dalam proses pembelajaran.